Potential drug-drug interactions in patients with indication for prophylactic implantation of a cardioverter defibrillator: a cross-sectional analysis - Christina Dornquast; Mirja Dombrowski; Markus Zabel; Stefan N. Willich; Thomas Reinhold (BMC, 2020)
Abstract Background Due to demographic transition, multimorbidity and high numbers of medicinal products, polypharmacy rates will presumably further increase. This could lead to higher risks of potentially inappropriate medications with potential drug-drug interactions (PDDI). PDDI has already been investigated by several studies, but not for patients with indication for prophylactic implantation of a cardioverter defibrillator (ICD). Thus, the objective of this analysis was to examine the frequency of PDDI in that specific group of patients and compare patients with or without PDDI regarding potential underlying factors. Methods Cross-sectional data analyses were performed using data of the prospective EU-CERT-ICD study that primarily aimed to assess ICD effectiveness in Europe. Self-reported baseline medication data of patients from Germany and Switzerland were used. Patients who reported to take at least two drugs simultaneously for at least 80 days were defined as population at risk. By means of a publicly available interaction checker, we analyzed the medication data regarding occurrence and characteristics of PDDI categorized as minor, moderate, and major PDDI. The analyses were done using descriptive methods and chi square testing. Results The total population (n = 524) and the population at risk (n = 383) were rather similar with an average age of 64 years and about 80% male. PDDIs were found for 296 patients (in 57% of total population vs. 77% of population at risk). The moderate PDDI category was most frequently with 268 affected patients. Comparing patients with and without any PDDI, the proportion of patients with place of residence in Germany varied distinctly (93% vs. 78%). The frequency of any PDDI for the total population was twice as high in Germany as in Switzerland (p value < 0.001). Conclusions PDDIs were frequently observed in this selected patient population and differed markedly between German and Swiss patients. The results should lead to higher awareness of polypharmacy and PDDIs. Adequate cooperation between health care providers should be promoted and new technologies such as drug interaction information systems or digital patient files used. Trial registration The EU-CERT-ICD study is registered at www.clinicaltrials.gov ( NCT02064192 ).